Teacher Perceptions of Learner-Learner Engagement at a Cyber High School - Borup, Jered (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2016)
Distance education has historically contained little or no learner–learner interactions. Currently the Internet allows for unprecedented levels of learner–learner interaction and has the potential to transform how students learn online. However, many courses offered online focus more on flexibility and independence than on interaction and collaboration. Often it is up to the teacher to decide how much learner–learner interaction their courses contain. However, little research has examined how online high school teachers perceive, value, and facilitate learner–learner interactions. This case study used teacher surveys and interviews at a full-time online charter high school to examine teacher perceptions of learner–learner interactions. The analysis identified four student behaviors that positively impact student engagement and learning: befriending, motivating, instructing, and collaborating. Teachers also identified several drawbacks to learner–learner interactions such as bullying and cheating. Furthermore, there appeared to be tension between providing for students’ individual needs and requiring collaborative learning opportunities.